On the competition between Video OTTs Platforms vs Traditional TV: A Niche Case Study in Greece - Athanasios Papathanasopoulos; Dimitris Varoutas (International Telecommunications Society (ITS), 2022)
The paper examines the competition between traditional TV and Video OTT platforms in Greece. The niche theory has been adopted in order to measure users' gratification fulfilled by TV and OTTs, the competition superiority of each media and the similarity of those two media across seven aspects of gratification. An online survey conducted during first months of 2022 and 355 total feedbacks has been collected. Video OTTs score higher in six dimensions of gratification than TV, except financial benefit. Regarding niche overlap, results show that those media share close levels of similarity in information, ease of use and convenience. OTT's exceed TV in five dimensions of gratification. The highest score on the overall findings of competition superiority is in relaxation, while TV exceeds in financial benefit and information.
Keywords: 330; media platform; media competition; niche analysis; OTT